PENGURANGAN KADAR AIR OPTIMAL (MOISTURE CONTENT) BLANKET SIR 10 MELALUI PROSES MATURASI DI PABRIK PENGOLAHAN KARET - Arga Dwi Ananda; Busrizal Faisal; Siti Aisyah (Jurnal Agro Fabrica, 2021)
Natural rubber processing is one of the potential agro-industrial sectors for Indonesia, whose role is quiteimportant as a foreign exchange earner for the plantation sub-sector. The production rate of 1.6 million tons in2002 or 22% of the world's total natural rubber production has placed Indonesia as the second largest producingcountry after Thailand. This study aims to determine whether the quality of blanket sir 10 is optimal by using amaturation time of 11 days, which is related to: Decreasing Blanket Moisture Content with Maturation Method,Analysis of Blanket Sample Data, Decreasing Water Content, Decreasing Blanket Moisture Content, MaturationProcess. The method of this research was carried out in a crumb rubber processing factory using a researchdesign: Bound variables Rubber sheet / blanket and crumb rubber from a rubber processing factory, theindependent variables in this study were as follows: Maturation treatment: hanging, maturation time: 11 days.The total weight of samples I, II, III, and IV is 975.90 kg, the total water content evaporated is 8.85 kg and theamount of blanket shrinkage is 0.91%. This shrinkage of the blanket amounted to 0.91%, which is the totaldecrease in the blanket moisture content in the eleven (11) days maturation. This process of maturing takes placenaturally. From data analysis and discussion of reducing the blanket moisture content for 11 days and processingmaterial for SIR 10 (Standard Indonesian Rubber) / Low Grade Crumb Rubber, it is concluded, as follows: Using4 (four types of samples with initial blanket weight: 20.15 kg) (sample 1), 20.85 kg (sample 2), 24.90 kg (sample3), and 27.85 kg (sample 4). Decreased moisture content in sample 1 = 1.06%, sample 2 = 0, 85%, sample 3 =0.87%, and sample 4 = 0.88%. The average reduction in water content in the blanket was 0.91% (for 11 days). Inthe reporting of this study, the blanket maturation time was set at 11 (eleven) days, although there are othermaturation times, such as: 6 (six) days, and 8 (eight days). The relatively h